Effect of short-term exposure to ambient air pollutants on non-accidental mortality in emergency department visits: a time-series study - Siting Wang; Yongming Zhang; Xia Li; Xia Li; Jinhua Zhao; Naijian Zhang; Yuming Guo; Jiageng Chen; Yuanyuan Liu; Zhuang Cui; Yuanjun Lyu; Jing Gao; et al. (Frontiers Media S.A., 2023)
ObjectivesExposure to air pollution has been linked to an increased risk of premature mortality. However, the acute effects of air pollution on the risk of non-accidental mortality have not been extensively researched in developing countries, and the findings thus far have been inconsistent. Therefore, this study aimed to examine the association between short-term exposure to six pollutants (PM2.5, PM10, SO2, NO2, O3, and CO) and non-accidental mortality in Beijing, China.MethodsDaily data on non-accidental deaths were gathered from 1 January 2017 to 31 December 2018. Air pollution data for the same period were collected from 35 fixed-site air quality monitoring stations in Beijing. Generalized additive models (GAM) based on Poisson regression were used to investigate the association between non-accidental mortality in emergency department visits and the daily average levels of air pollutants.ResultsThere were 8,676 non-accidental deaths recorded during 2017-2018. After sensitivity analysis, short-term exposure to air pollutants, particularly gaseous pollutants, was linked to non-accidental mortality. Specifically, for every 10 μg/m3 increase (5 μg/m3 in SO2, 0.5 mg/m3 in CO) of SO2 (lag 04), NO2 (lag 04), O3 (lag 05), and CO (lag 04), the relative risk (RR) values were 1.054 (95% CI: 1.009, 1.100), 1.038 (95% CI: 1.013, 1.063), 1.032 (95% CI: 1.011, 1.054), and 1.034 (95% CI: 1.004, 1.066), respectively. In terms of causes of death, short-term exposure to NO2, SO2, and O3 increased the risk of circulatory mortality. Further stratified analysis revealed that the stronger associations were presented in females for O3 while in males for CO. People aged 65 and over were strongly associated with ambient air pollution.ConclusionsOur study showed that ambient air pollutants were associated with non-accidental mortality. Our findings suggested that efforts to control gaseous pollution should be stepped up, and vulnerable groups should be the focus of health protection education.